2022
DOI: 10.1186/s12889-022-13189-7
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of and attitudes towards HIV testing for Asian, Black and Latin American men who have sex with men (MSM) in the SELPHI (HIV Self‐Testing Public Health Intervention) randomized controlled trial in England and Wales: implications for HIV self-testing

Abstract: Background HIV self-testing (HIVST) could play an important role in improving access to testing and therefore reducing inequalities related to late diagnosis of HIV, while also improving access to HIV prevention interventions such as HIV pre-exposure prophylaxis. This study sought to understand the potential role of HIVST by exploring the experiences of Asian, Black and Latin American men who have sex with men (MSM) accessing the gay scene and the circulation of HIV testing norms; experiences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
4
12
0
Order By: Relevance
“…Several studies have reported high acceptability, including by transgender communities and for Asian, Black, and Latin American gay and bisexual men. COVID‐19 could easily have further increased the acceptability of home testing by normalizing the use of similar technologies [25, 26].…”
Section: Advantages Of Self‐testingmentioning
confidence: 99%
“…Several studies have reported high acceptability, including by transgender communities and for Asian, Black, and Latin American gay and bisexual men. COVID‐19 could easily have further increased the acceptability of home testing by normalizing the use of similar technologies [25, 26].…”
Section: Advantages Of Self‐testingmentioning
confidence: 99%
“…More importantly, differences in access to infrastructure (road, water, electricity, and health facilities) around urban and rural districts widen the disparities, observed from the outcome of the study [ 8 , 55 ]. Furthermore, due to urbanisation and conflict across the globe, migration contributes to diverse cultures which to some extent influence people’s attitudes and knowledge in society towards HIV/AIDS self-testing uptake [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition, there has been an increase in new HIV diagnoses among newly arrived people born in Latin America or Caribbean in Australia. [32][33][34] Because of cultural factors, stigma, and discrimination, people from these regions may have limited access to sexual health information and resources [35][36][37] ; important sexual health messages and education can be delivered to these clients via SHAVE, and they can review these resources in their private own time to reduce embarrassment and shame.…”
Section: Discussionmentioning
confidence: 99%